2019
DOI: 10.1158/1078-0432.ccr-18-0655
|View full text |Cite
|
Sign up to set email alerts
|

Classes of ITD Predict Outcomes in AML Patients Treated with FLT3 Inhibitors

Abstract: Recurrent internal tandem duplication (ITD) mutations are observed in various cancers including acute myeloid leukemia (AML), where ITD mutations in tyrosine kinase receptor FLT3 are associated with poor prognostic outcomes. Several FLT3 inhibitors (FLT3i) are in clinical trials for high-risk -ITD-positive AML. However, the variability of survival following FLT3i treatment suggests that the mere presence of-ITD mutations might not guarantee effective clinical response. Motivated by the heterogeneity of -ITD mu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 52 publications
1
19
1
Order By: Relevance
“…Consistent with the above data, the IC 50 of D835Y reflects an enhanced level of sensitivity to Gilteritinib. These data reflect the known sensitivities of cells bearing FLT3-ITDs in response to these two TKI inhibitors [17,20,[40][41][42].…”
Section: Resultssupporting
confidence: 69%
“…Consistent with the above data, the IC 50 of D835Y reflects an enhanced level of sensitivity to Gilteritinib. These data reflect the known sensitivities of cells bearing FLT3-ITDs in response to these two TKI inhibitors [17,20,[40][41][42].…”
Section: Resultssupporting
confidence: 69%
“…In this issue of Clinical Cancer Research, Schwartz and colleagues show that structural features of FLT3-internal tandem duplications (ITDs) mutations, a highly recurrent mutation in acute myeloid leukemia (AML), influence patient responses and overall outcome following both standard cytotoxic chemotherapy and targeted FLT3 inhibitor therapy(1).…”
Section: Commentarymentioning
confidence: 99%
“…A recent study indicated that nucleotide composition of ITDs, particularly the presence of nontemplated nucleotide content, may impact response to FLT3 inhibition and induction chemotherapy, whereas prior studies have reported inferior outcomes associated with ITDs extending into tyrosine kinase domain 1 or located closer to the C-terminus. 9 , 22 , 33 , 34 By using this algorithm, a case was encountered with a 30-bp ITD at initial diagnosis along with a 180-bp ITD extending into tyrosine kinase domain 1, where the 30-bp ITD subsequently disappeared on treatment while the 180-bp subclone persisted at low level. The clinical significance is uncertain; however, the case highlights the potential utility of comprehensive ITD analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Although the development of specialized FLT3 -ITD algorithms has improved recognition of mutant reads, few studies have adequately addressed AR estimation and some algorithms are limited to specific NGS platforms. 14 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 In particular, a trend for AR underestimation by NGS relative to CE has been consistently shown. 17 , 21 , 24 , 25 …”
mentioning
confidence: 90%